2005
DOI: 10.1103/physrevb.71.024522
|View full text |Cite
|
Sign up to set email alerts
|

From incommensurate to dispersive spin-fluctuations: The high-energy inelastic spectrum in superconductingYBa2Cu3O6.5

Abstract: We have investigated the spin fluctuations at energy transfers up to ∼ 110 meV, well above the resonance energy (33 meV) in the YBa2Cu3O6.5 ortho-II superconductor using neutron timeof-flight and triple-axis techniques. The spectrum at high energies differs from the low-energy incommensurate modulations previously reported where the incommensurate wave vector is largely independent of energy. Well above the resonance the peak of the spin response lies at wave vectors that increase with energy. Within error the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
199
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(222 citation statements)
references
References 53 publications
20
199
2
Order By: Relevance
“…Inelastic neutron scattering studies are consistent with an "hour glass" dispersion, wherein low energy spin excitations disperse out of IC wavevectors and merge or nearly-merge at the C wavevector to form a resonant spin excitation [23][24][25][26][27][28][29][30] . At higher energies, the excitations disperse out from the C wavevector, before turning over near the Brillouin zone boundaries 23,31,32 . Such a picture has been shown to be relevant even in the relatively low hole-doping regime of La 2−x Sr x CuO 4 , where the insulating ground state is characterized by socalled "diagonal" IC spin order 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Inelastic neutron scattering studies are consistent with an "hour glass" dispersion, wherein low energy spin excitations disperse out of IC wavevectors and merge or nearly-merge at the C wavevector to form a resonant spin excitation [23][24][25][26][27][28][29][30] . At higher energies, the excitations disperse out from the C wavevector, before turning over near the Brillouin zone boundaries 23,31,32 . Such a picture has been shown to be relevant even in the relatively low hole-doping regime of La 2−x Sr x CuO 4 , where the insulating ground state is characterized by socalled "diagonal" IC spin order 33 .…”
Section: Introductionmentioning
confidence: 99%
“…[46] demonstrated that, for the incommensurate scattering at an energy corresponding to 70% of the saddle point, the intensity is quite anistropic, with maxima along the a * direction (perpendicular to the orientation of the CuO chains). A recent study of an array of highly detwinned crystals of YBa 2 Cu 3 O 6.85 by Hinkov et al [29] found substantial anisotropy in the peak scattered intensity for an energy of 85% of the saddle point, but also demonstrated that scattered intensity at that energy forms a circle about Q AF [see by Stock et al [47,28] suggest a strong anisotropy in the scattered intensity at 0.36E r , but essentially perfect isotropy for E > E r .…”
Section: Dispersionmentioning
confidence: 99%
“…8.3 is striking, and suggests that the magnetic dispersion spectrum may be universal in the cuprates [40,44]. Christensen et al [40], in La1.875Ba0.125CuO4 (filled circles) from [42], and in YBa2Cu3O6+x with x = 0.5 (squares) from Stock et al [28] and 0.6 (diamonds) from Hayden et al [27]. The energy has been scaled by the superexchange energy J for the appropriate parent insulator as given in For optimally doped YBa 2 Cu 3 O 6+x , the measured dispersive excitations are restricted to a narrower energy window, as shown in Fig.…”
Section: Dispersionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we compare the formation of a resonant spin excitation (the "resonance peak") in three different ordered states: the DDW phase, the d x 2 −y 2 -wave superconducting (DSC) phase, and a phase with coexisting DDW and DSC order. The observation of the resonance peak in inelastic neutron scattering (INS) experiments 7,8,9,10,11,12,13,14,15 is one of the key experimental facts in the phenomenology of the high-T c cuprates. In the optimally and overdoped cuprates, the resonance peak appears below T c in the dynamical spin susceptibility at the antiferromagnetic wave vector Q = (π, π).…”
Section: Introductionmentioning
confidence: 99%